2021
DOI: 10.2174/1574888x15999200918110638
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Isolated from Mesenchymal Stromal Cells Primed with Hypoxia: Novel Strategy in Regenerative Medicine

Abstract: : Mesenchymal stromal cells (MSCs) regulate other cell types through a strong paracrine component called the secretome, comprising of several bioactive entities. The composition of the MSCs’ secretome is dependent upon the microenvironment in which they thrive, and hence, it could be altered by pre-conditioning the MSCs during in vitro culture. The primary aim of this review is to discuss various strategies that are being used for pre-conditioning of MSCs, also known as “priming of MSCs”, in the context of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In independent studies, we have also demonstrated that MVs secreted by the MSCs boost the engraftment ability of HSCs, rejuvenate aged HSCs, and enhances the ability of HSCs to expand in vitro [17], [20], [21], [58]. Based upon these ndings, we are currently investigating the differential role of MSC CM-derived MVs and exosomes in enhancing the ex vivo expansion potential and in vivo engraftment potential of HSCs.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In independent studies, we have also demonstrated that MVs secreted by the MSCs boost the engraftment ability of HSCs, rejuvenate aged HSCs, and enhances the ability of HSCs to expand in vitro [17], [20], [21], [58]. Based upon these ndings, we are currently investigating the differential role of MSC CM-derived MVs and exosomes in enhancing the ex vivo expansion potential and in vivo engraftment potential of HSCs.…”
Section: Discussionmentioning
confidence: 93%
“…In ammation is one of the major factors responsible for the pathogenesis of ND Previously, we have reported the importance of MSCs and their secretome as potential therapeutics for ND[16], [24] as well as for improving the ex vivo expansion of HSCs [17], [21]. Presently, researchers are taking a step forward by adopting priming strategies to enhance the regenerative potential of MSCs and their secretome [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell priming (here called biochemical pulse pattern, abbreviated as bio-pulsed) involves preparing cells for lineage-specific differentiation or conferring the cells with specific functions through cell activation, molecular signaling activation, genetic or epigenetic modifications, and morphology/phenotype alterations. Recently, studies have reported that the composition of the MSCs’ extracellular vesicles or exosomes is dependent upon the microenvironment in which they thrive, and hence it can be altered by pre-conditioning or priming the MSCs during in vitro culture [ 25 ]. MSCs were primed with pro-inflammatory cytokines or hypoxia; primed-MSCs derived extracellular vesicles or exosomes that were isolated and reported with special functions, such as anti-inflammation or better therapeutic efficiency [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%